2011
DOI: 10.4028/www.scientific.net/ddf.312-315.554
|View full text |Cite
|
Sign up to set email alerts
|

Partition of Free Fatty Acids in Deacidification of Macaúba Pulp Oil by Liquid-Liquid Extraction Using Ethanol/Water as Solvent

Abstract: Free fatty acids (FFA) is one of the most frequently determined quality indices in fats and oils industry because it has the economic impacts on production [1]. The FFA in macaúba pulp oil is usually very high (10 to 40%) due to enzymatic activity in the raw material [2]. In this case, alkali neutralization is not economically recommended due to neutral oil loss by occlusion in soapstock. The differential solubility of fatty acids and triacylglycerides (TAG) in various organic solvents has formed the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…Regarding the chemical composition, studies have shown high levels of β-carotene (Ramos et al, 2008;Rocha et al, 2013;Sanjinez-Argandoña and Chuba, 2011), α-tocopherol Jorge, 2011, 2012) and oleic acid (Amaral et al, 2011;Mariano et al, 2011) in the A. aculeata pulp performed by high-performance liquid chromatography and open column procedures. Though widely used by the population and favored for its nutritional and medicinalchemistry purposes, little information is available in the literature on the therapeutic or toxic effects of this species.…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the chemical composition, studies have shown high levels of β-carotene (Ramos et al, 2008;Rocha et al, 2013;Sanjinez-Argandoña and Chuba, 2011), α-tocopherol Jorge, 2011, 2012) and oleic acid (Amaral et al, 2011;Mariano et al, 2011) in the A. aculeata pulp performed by high-performance liquid chromatography and open column procedures. Though widely used by the population and favored for its nutritional and medicinalchemistry purposes, little information is available in the literature on the therapeutic or toxic effects of this species.…”
Section: Introductionmentioning
confidence: 97%
“…ex Mart., popularly known as ''bocaiúva'' or ''macaúba'', is a plant that is widely distributed in the midwest region of Brazil (Lorenzi, 2006). Analysis of the fruit pulp of A. aculeata by high-performance liquid chromatography revealed the presence of high levels of antioxidants such as β-carotene (Ramos et al, 2008;Sanjinez-Argandoña and Chuba, 2011;Rocha et al, 2013), α-tocopherol (Coimbra and Jorge, 2011), and monounsaturated fatty acids such as oleic acid (Amaral et al, 2011;Mariano et al, 2011). Antioxidants are important in the prevention of age-associated degenerative diseases (Barreiros et al, 2006;Gama and Sylos, 2007;Nagaraju and Lokesh, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This partitioning had already been observed in earlier studies (Batista et al, 1999;Shiozawa et al, 2015). The liquid-liquid extraction by ethanol has been especially studied as an alternative method of vegetable oil deacidification (Mariano et al, 2011, Rodrigues et al, 2006, Cuevas et al, 2009. These studies were mainly focused on free fatty acid elimination from the oil.…”
Section: Lipid Compositionmentioning
confidence: 99%